Optimizing of a Horizontal Cylinder Type Cocoa Roaster for Dried Cocoa Cotyledon Roasting - Sukrisno Widyotomo; Sri Mulato; Edi Suharyanto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2006)
The secondary process of cocoa is one of the promising alternatives to increase the value added of dried cocoa beans. One the other hand, the development for secondary cocoa process requires an appropriate technology that is not available yet for small or medium scale business. Cocoa roaster is a basic equipment to produce good and competitive secondary cocoa products for chocolate industry. The Indonesian Coffee and Cocoa Research Institute has, therefore, designed and tested a horizontal cylinder type roaster for drying cocoa cotyledon. The cylinder has 405 mm diameter, 520 mm long and is rotated by a 1 HP (0.75 kW), 220 V, single phase and 1400 rpm electric motor. Assisted with a gear reducer, the final cylinder rotation is adjusted at approximately 6 rpm. The heat for roasting process is generated from kerosene burner. At the end of roasting, the roasted beans are cooled down by ambient air inside a cooling platform by natural air flow. The raw material used in this optimizing test was dried fine cocoa cotyledon. Field tests showed that the optimum performance of the roaster was 7 kg dried fine cocoa cotyledon loaded with roasting temperature 120 oC and 25.57 kg/h optimum capacity. The organoleptic test showed that score of aromatic, flavour, acidity, bitterness, astringency and burnt were 4.8, 5.2, 5.4, 5.2, 4.8 and 0.8 with 10 scale, also 4.2 with 5 scale for likely. The roasting time was 15—25 minutes to get 2.5—3% final water content depend on roasting temperature and cocoa cotyledon loaded. Key words: cocoa, roasting, horizontal cylinder, quality.